Hemostatic topical oxidized cellulose effect on blood clots after mandibular molar extraction at Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Universitas Sumatera Utara - Ahyar Riza; Ibnul Qayyim (Journal of Dentomaxillofacial Science, 2022)
Objective: In the act of extracting teeth, the discharge of blood cannot be avoided. This can be overcome normally because of the hemostatic process that stops bleeding. One ingredient to help with the process of hemostatic is the hemostatic material topically oxidized cellulose. This study aims to determine the effect of topical hemostatic administration of oxidized cellulose on blood clotting after extraction of mandibular molars. Material and Methods: This study was an experimental study using 2 sample groups, consisting of 19 patients per group. Results: The results of the study were analyzed using the Independent T Test and Shapiro-Wilk test. The treatment group had a shorter blood coagulum time p=0.0000001 (p<0.05). Conclusion: This shows that there is an effect of giving topical cellulose hemostatic material to blood clotting after tooth extraction.